Total glucosides of paeony ameliorates chemotherapy-induced neuropathic pain by suppressing microglia pyroptosis through the inhibition of KAT2A-mediated p38 pathway activation and succinylation - Rong Chen; Jiantao Hu; Yang Zhang; Yang Liu; Jingsong Zhu; Zheng Pan; Hua Yang; Qin Wang; Ying Chen; Songjiang Tang; Baojun Min (Scientific Reports)
Abstract Chemotherapy-induced neuropathic pain (CINP) is a prevalent side effect of chemotherapy. Total glucosides of paeony (TGP) have been shown to be effective in pain management. This study aimed to investigate the efficacy and mechanism of TGP in alleviating CINP. Sprague–Dawley rats were treated with oxaliplatin to establish CINP models, and BV2 microglia were exposed to lipopolysaccharides (LPS) to induce pyroptosis. The impact of TGP on CINP was assessed by measuring mechanical withdrawal threshold (MWT), cold pain threshold (CPT), and thermal pain threshold (TPT), as well as inflammatory factor levels. Pyroptosis was evaluated using flow cytometry, lactate dehydrogenase (LDH) release, and pyroptosis marker levels. Quantitative real-time PCR and molecular docking were employed to identify TGP targets, while phospho-kinase arrays, western blotting, and co-immunoprecipitation were used to elucidate the mechanism. Results indicated that TGP increased MWT, CPT, and TPT and inhibited inflammatory factor release in CINP rats. Furthermore, TGP suppressed LPS-induced pyroptosis and downregulated KAT2A expression in BV2 cells; this suppression was reversed by KAT2A overexpression. Mechanistically, KAT2A overexpression activated the p38 pathway and promoted p38 succinylation at K295. KAT2A knockdown inhibited pyroptosis in LPS-induced BV2 cells, an effect that was reversed by the p38 activator metformin. Additionally, the improvements in MWT, CPT, TPT, and inflammatory factor levels observed in CINP rats treated with TGP were negated by KAT2A overexpression. In conclusion, TGP alleviated CINP by suppressing microglial pyroptosis through inhibition of the KAT2A-mediated p38 pathway activation and succinylation. This study provides insights into a potential new therapeutic approach for CINP.